Spatiotemporal variables of able-bodied and amputee sprinters in men`s 100-m sprint - Hobara, H.; Kobayashi, Y.; Mochimaru, M. (International Journal of Sports Medicine, 2015)
The difference in world records set by able-bodied sprinters and amputee sprinters in the men`s 100-m sprint is still approximately 1?s (as of 28 March 2014). Theoretically, forward velocity in a 100-m sprint is the product of step frequency and step length. The goal of this study was to examine the hypothesis that differences in the sprint performance of able-bodied and amputee sprinters would be due to a shorter step length rather than lower step frequency. Men`s elite-level 100-m races with a total of 36 able-bodied, 25 unilateral and 17 bilateral amputee sprinters were analyzed from the publicly available internet broadcasts of 11 races. For each run of each sprinter, the average forward velocity, step frequency and step length over the whole 100-m distance were analyzed. The average forward velocity of able-bodied sprinters was faster than that of the other 2 groups, but there was no significant difference in average step frequency among the 3 groups. However, the average step length of able-bodied sprinters was significantly longer than that of the other 2 groups. These results suggest that the differences in sprint performance between 2 groups would be due to a shorter step length rather than lower step frequency.